Feasibility assessment of yttrium-90 liver radioembolization imaging using amplitude-based gated PET/CT. Issue 3 (March 2018) - Osborne, Dustin R.; Acuff, Shelley N.; Neveu, Melissa L.; Syed, Mumtaz; Kaman, Austin D.; Fu, Yitong
Abstract : Purpose: The usage of PET/computed tomography (CT) to monitor hepatocellular carcinoma patients following yttrium-90 ( 90 Y) radioembolization has increased. Respiratory motion causes liver movement, which can be corrected using gating techniques at the expense of added noise. This work examines the use of amplitude-based gating on 90 Y-PET/CT and its potential impact on diagnostic integrity. Patients and methods: Patients were imaged using PET/CT following 90 Y radioembolization. A respiratory band was used to collect respiratory cycle data. Patient data were processed as both standard and motion-corrected images. Regions of interest were drawn and compared using three methods. Activity concentrations were calculated and converted into dose estimates using previously determined and published scaling factors. Diagnostic assessments were performed using a binary scale created from published 90 Y-PET/CT image interpretation guidelines. Results: Estimates of radiation dose were increased ( P <0.05) when using amplitude-gating methods with 90 Y PET/CT imaging. Motion-corrected images show increased noise, but the diagnostic determination of success, using the Kao criteria, did not change between static and motion-corrected data. Conclusion: Amplitude-gated PET/CT following 90 Y radioembolization is feasible and may improve 90 Y dose estimates while maintaining diagnostic assessment integrity.